Iron Metal Ion Adsorption Capacity on Palm Oil Mill Effluent (POME) Using Montmorillonite Adsorbent - Maria Dayanti Mellanie; Tisna Harmawan; Puji Wahyuningsih (The Journal of Pure and Applied Chemistry Research, 2022)
Palm oil mill effluent (POME) is the most produced waste among other types of waste, which is around 60% in every 100% processing of fresh fruit bunches containing heavy metals, namely ferrous metal (Fe). Montmorillonite (MMT) is one of the best adsorbents used to reduce the concentration of Fe in POME. In this study, the determination of the mass variation of the MMT as adsorbent and the variation of the contact time on the adsorption ability of Fe metal in POME was determined using an Atomic Absorption Spectrophotometer (AAS) and surface morphology analysis of MMT before and after adsorption using Scanning Electron Microscope (SEM). Based on the results of AAS analysis showed that greater the mass of the adsorbent then greater the amount of Fe from the POME that is adsorbed, and with variations in contact time that the longer the contact time between MMT and Fe then greater the amount of Fe in the palm oil mill effluent adsorbed on the adsorbent surface. The best adsorption conditions occurred at an adsorbent mass of 8.5 g MMT and a contact time of 5 hours with an adsorption capacity of 0.0383 mg/g. The results of the SEM showed the presence of empty spaces in the MMT before adsorption while after adsorption there were white granules that occupied the empty spaces evenly on the surface of the MMT. The granules indicate the presence of metals in the POME samples which are adsorbed on the MMT surface.